The Governance of Tax Audit Enforcement: Indicators on Automation Incentive, Tax Avoidance and Firm Characteristics - Halizam A. Hamzah, Fairus; Abd Hamid, Nadiah; Noor Hayati Mohd Zawawi, Siti; Jaafar, Salmah; Md Azali, Norazah (KnE Social Sciences, 2019)
The intense development in the Fourth Industrial Revolution (IR 4.0) demands tight governance of tax audit enforcement by the Inland Revenue Board Malaysia (IRBM) on firms claiming automation incentive. Through tax audit enforcement, IRBM provides a monitoring mechanism for corporate governance. However, due to data confidentiality, little has been established on what indicators that caused tax authority to carry out tax audits. In this research, we employed tax return and historical audit data of corporate taxpayers consisting of profitable and loss firms which consistently claim the Reinvestment Allowance (RA) to examine the indicators applied by the tax authority in executing the role of governance. Employing Binary logistic regression, firm characteristic of firms experiencing tax audit was observable, but tax avoidance and incentive utilization indicators were not apparent. Tax avoidance indicators such as effective tax rate and book-tax difference, loss firms, and incentive utilization receive less attention when it comes to tax audit enforcement. Examining firms that experienced tax audit enforcement has enriched our understanding of indicators that draw the interest of tax authorities when it comes to tax audits. Overall, this research could be the first in Malaysia that has used actual historical tax audit record, which has revealed new evidence on the indicators preferred by the IRBM in conducting a tax audit. The slight fine-tuning of the responses, especially on tax avoidance and incentive utilization indicators for tax enforcement might produce comprehensive tax audit coverage and yield a greater mechanism for governance.